THE INFLUENCE OF MANAGERIAL OWNERSHIP TOWARD THE VALUE OF FIRM WITH THE FINANCING DECISION AS AN INTERVENING VARIABLE - Ikaprasetyawati Nur Lillahirani; Erida Herlina (STIE Perbanas Surabaya, 2013)
Every company has the same goal that is to maximize the value of the company and thewealth of its shareholders. Due to the different interests between the shareholders and themanagement, there is always conflict in the company. Share ownerships by the companymanagement is believed to be able to unite the interest between the shareholders and themanager, therefore at the end, it results in the company performance in achieving companygoals. Funding decision is a structure that has to be implemented by the management correctlyso that the value of the company can increase. This research uses 130 manufacturecompanies that listed on Indonesian Stock Exchange by the year of 2010. The method tochoose the samples is done by using purposive sampling method and path analysis method.The result of this research show that: 1) managerial ownership effect directly the companyvalue, 2) funding decision does not affect the company value, 3) managerial ownership effectthe company value with funding decision as its intervening variable and it is approved thatfunding decision is used to find the effect of managerial ownership on the company value.